Noruz: treading time, nature, culture and faith - Zekrgoo, Amir Hossein (Sekolah Tinggi Fisafat Islam Sadra, 2015)
Noruz, astronomical vernal spring equinox, is the 1st day in the Persian Islamic solar calendar. It is among the oldest celebrations in history that is still alive and observed by various peoples. In 2009 UNESCO declared Noruz as an Intangible Cultural Heritage of Humanity and in 2010 The United Nations General Assembly recognized the International Day of Noruz, describing it as a” festival of Persian origin which has been celebrated for over 3,000 years.” To this day Noruz is observed in Iran, Afghanistan, parts of Central Asia, Caucasus, South Asia (Indian subcontinent), Northwestern China, the Crimea and some parts in Balkans. Moreover, the festival of Noruz is tightly connected to the cycle of nature and is scientifically regarded as the most accurate mark of the spring equinox, hence the beginning point of a very precise calendar system. Closely associated with the pulse of natural creation and the tempo of time, Noruz gradually transcended the geographical barriers and became a cultural event that celebrated the rebirth of nature and a thanksgiving to the Creator. The celebration of Noruz can therefore be traced in the festivities held by followers of pre-Islamic Abrahamic faiths. After the advent of Islam for a while Noruz became a subject of debate; some writers criticized its pre-Islamic origin while others responded to it favorably as its celebration did not oppose the tenets of Islam. There are records of the celebration of Noruz in the Islamic history as early as the Abbasid Caliphate. The renown Muslim scholar, Abū Rayhān Birūnī (10th Cent. AD), provides a description of the calendars of various nations and refers to Noruz and refers to a hadith describing the Prophet blessing the day as the occasion of renovation of life. Noruz survived the turbulences of time and remained as an Islamized cultural celebration among many Muslims that historically share Persian culture. This research presents a multifaceted approach to the subject: historical, religious, symbolic and scientific. It is aimed at tracing Noruz in the history, its significance in the setting of an accurate solar calendar, its evolvement in various religious traditions and, eventually, the process of its Islamization. It also provides an analytical account of the ‘Haft-sīn Spread’ – a setting of seven items that are closely associated with the celebration of Noruz – and their symbolic significance. Keywords: Noruz, Haft-Sīn, Festival, Purim, Easter, Islamic Solar Calendar, Intangible Cultural heritage, Vernal Spring Equinox